The role of ecological interactions in determining species ranges and range changes. (15th April 2015) - Stewart, Alan J. A.; Bantock, Tristan M.; Beckmann, Björn C.; Botham, Marc S.; Hubble, David; Roy, David B.
<x xml:space="preserve">Abstract</x> Climate has been widely regarded as the main determinant of the geographical distribution of species. Biotic interactions between co‐occurring species, however, are an important additional influence. We review the importance of interactions with food and nectar plants (as resources) in determining the distribution of phytophagous and pollinating insects (as consumers). We use biological recording datasets for seven taxonomic groups to quantify the relationship between the geographical distributions within Britain of 1265 phytophagous insects and their associated food plants, representing 9128 interactions in total. We find a consistent pattern across taxonomic groups in that individual phytophagous insect species rarely utilize the full range of their food plants and the relationship between the range sizes of insects and their food plants is not a simple linear one. For a small selection of phytophagous species where data are available, we highlight an association between changes in range and interactions with associated food plant species. Climate‐driven range expansion may be constrained through disruption of trophic relationships between phytophagous insects and their food plants if they respond differently to abiotic drivers. By contrast, range expansion may be facilitated by temporary escape from natural enemies and/or exploitation of novel food plants that enable a broader set of habitats to be utilized. In a changing environment, some existing interactions will be disrupted but opportunities for novel interactions will also emerge, producing new assemblages and changes in distributions that will be dynamic yet hard to predict. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, ●●, ●●–●●.